A Practice-Oriented Review of Health Concepts. Issue 4 (9th July 2018) - Haverkamp, Beatrijs; Bovenkerk, Bernice; Verweij, Marcel F
Abstract: Whereas theories on health generally argue in favor of one specific concept, we argue that, given the variety of health practices, we need different concepts of health. We thus approach health concepts as a Wittgensteinian family of thick concepts. By discussing five concepts of health offered by (philosophical) theory, we argue that all capture something that seems relevant when we talk and think about health. Classifying these concepts reveals their family resemblances: each of these concepts differs from the others in at least one respect and resembles the others in several respects. Moreover, our classification shows that "health" always both describes a condition and evaluates that condition at the same time. Having both descriptive and evaluative dimensions, we can see health concepts as "thick concepts." It is because of this evaluative dimension that it is important to reflect on the question of what understanding of health guides specific practices. We show that the distinctions revealed by our classification can serve as a conceptual toolbox for reflection on the assumptions and purposes of particular health practices. Finally, we illustrate how such reflection could work out by briefly exploring three specific health practices.